2019
DOI: 10.1016/j.ecresq.2018.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Effects of geometric toy design on parent–child interactions and spatial language

Abstract: Geometric forms have formal definitions. While knowing shape names is considered important for school-readiness, many children do not understand the defining features of shapes until well into elementary school (Satlow & Newcombe, 1998). One reason is likely that they do not encounter enough variety in the shapes they see (citation removed). The present study observed 60 parents and their 3-year-old children during play with geometric toys, exploring how spatial language varied with the nature of the shape-toy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…In one experimental manipulation, Polinsky et al (2017) found that providing parents with prompts to discuss spatial content while playing with their children at a museum led to increases in parents' spatial talk as well as children's spatial talk and, in turn, children's performance on a spatial task. Furthermore, much like parental number talk, the frequency of parents' spatial talk varies systematically across different types of activities (Ferrara et al, 2011;Zosh et al, 2015;Ho et al, 2018;Lee et al, 2019;Verdine et al, 2019;. We extend this further by considering the relations between frequencies of number and spatial talk between parents and children as they engage in different activities.…”
Section: Observations Of Parental Math Talkmentioning
confidence: 86%
“…In one experimental manipulation, Polinsky et al (2017) found that providing parents with prompts to discuss spatial content while playing with their children at a museum led to increases in parents' spatial talk as well as children's spatial talk and, in turn, children's performance on a spatial task. Furthermore, much like parental number talk, the frequency of parents' spatial talk varies systematically across different types of activities (Ferrara et al, 2011;Zosh et al, 2015;Ho et al, 2018;Lee et al, 2019;Verdine et al, 2019;. We extend this further by considering the relations between frequencies of number and spatial talk between parents and children as they engage in different activities.…”
Section: Observations Of Parental Math Talkmentioning
confidence: 86%
“…However, it is also of interest if children's Mass knowledge can be supported in regard to their developmental constraints. Playful interventions with building blocks have supported the acquisition of different mathematical and spatial skills in other studies (e.g., Ferrara et al, 2011;Fisher et al, 2013;Borriello and Liben, 2018;Thomson et al, 2018;Verdine et al, 2019).…”
Section: The Statics Domain and Children's Beliefs About Balancementioning
confidence: 81%
“…Promoting young children’s science learning aims at helping them adjust their theories and should consider children’s developmental constraints by considering children’s everyday activities, e.g., their play ( Copple and Bredenkamp, 2009 ). One possibility for such science-related play could be construction play in the form of block play, which is an important leisure activity for young children ( Rubin et al, 1978 ; Pellegrini and Gustafson, 2005 ; Borriello and Liben, 2018 ; Verdine et al, 2019 ). An adult’s guidance might be integrated into children’s play in the form of scaffolding, which might support children’s science learning (cf.…”
Section: Introduction: Science Educationmentioning
confidence: 99%
“…In an interactive and entertaining setting, active exploration was stimulated with the use of real objects, placed in different space plans, and through verbal guidance also exposing the child to spatial language (e.g., spatial location words like “up” or “down,” deictic terms like “here” or “there,” dimensions, shape terms, spatial orientations, etc.). This use of language seems to help to elicit more spatial language production and to build later skills such as the ability to do spatial transformations and analogies ( Verdine et al, 2019 ) and it is recommended also in parent-child interactions. Playing with toys that incorporate shapes (e.g., shape sorters), labeling them, and discussing shape properties may be among the earliest spatial experiences parents provide ( Verdine et al, 2016 ).…”
Section: Methodological Aspectsmentioning
confidence: 99%